Cognitive Development Of National Insight Through Visual Interactive Methods Toward Indonesian Children In Malaysia - Wardhatul Livia; Milla Maulida Izzah; Rafi Pramana Putra; St.Nuradinda Wahyudiarti; Siti Nur Azizah (Universitas Muhammadiyah Purwokerto, 2025)
Migrant workers in Malaysia are a concern so the spirit of nationalism needs to be maintened by every Indonesian citizen. The phenomenon of the younger generation paying less attention to national literacy is caused by being more interested in visual media. Children's cognitive development can be obtained from interactive visual learning. The purpose of this service is to contribute to the development of innovative national education methods that are according to the needs of the digital generation and can improve children's cognitive abilities. The implementation method combines two mixed methods of interactive visuals and traditional Domikado games. This activity targets Indonesian children aged 5-6 years in Sentul Malaysia with international collaboration of volunteers by youth. id and Semangat Muda Indonesia in November 2024. The results were that children actively participated in a series of activities and were more confident in expressing answers to each question given. In addition, children could review the material taught quickly and accurately. The mixed interactive visual method effectively improves children's cognitive abilities, including national insight.